2021
DOI: 10.1111/vde.12974
|View full text |Cite
|
Sign up to set email alerts
|

Multivariable analysis of the influence of cross‐reactive carbohydrate determinant inhibition and other factors on intradermal and serological allergen test results: a prospective, multicentre study

Abstract: Background -Serological allergen testing (SAT) is used widely to formulate allergen-specific immunotherapy for atopic dogs. Serum immunoglobulin (Ig)E specific for cross-reactive carbohydrate determinants (CCD) can produce false-positive reactions, creating discrepancy between SAT and intradermal allergen test (IDAT) results.Objectives -The primary objective was to determine if inhibition of anti-CCD IgE in a commercial assay improved correlation with IDAT. The secondary objective was to assess the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 32 publications
0
27
3
Order By: Relevance
“…Use of LVM over a six‐month period (in the LVM group) may have resulted in a decrease in AsIgE concentrations. A recent study reported a slight reduction in AsIgE associated with LVM use; however, the dose used was higher (median 2.37 mg/kg) than that used in our study and in some cases the duration of therapy was longer (median four weeks; range 1–140 weeks) 40 …”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Use of LVM over a six‐month period (in the LVM group) may have resulted in a decrease in AsIgE concentrations. A recent study reported a slight reduction in AsIgE associated with LVM use; however, the dose used was higher (median 2.37 mg/kg) than that used in our study and in some cases the duration of therapy was longer (median four weeks; range 1–140 weeks) 40 …”
Section: Discussioncontrasting
confidence: 75%
“…A recent study reported a slight reduction in AsIgE associated with LVM use; however, the dose used was higher (median 2.37 mg/kg) than that used in our study and in some cases the duration of therapy was longer (median four weeks; range 1-140 weeks). 40 In this study, the used protocol combining ILIT with LVM was found to be a safe therapy for atopic dogs. Although results of this ILIT protocol were comparable with LVM monotherapy in this study, we were not able to show an advantage over other ILIT protocols used in other studies.…”
Section: Discussionmentioning
confidence: 80%
“…Objective and subjective scoring have been shown previously to have varying degrees of agreement depending on the threshold that was used to define an objectively positive skin test reaction 11,16,21,26,27 . Indeed, there has been only slight 21,26 to no 27 agreement between subjective IDT scores and objective IDT scores of clinical significance (subjective scores ≥2) reported in several prior studies, which utilised MWD for IDT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on available evidence and known mechanisms of action, dogs currently receiving or having previously received ciclosporin, lokivetmab or oclacitinib were not excluded 13–15 . In addition, a multi‐institutional study has shown that long‐term use of these drugs does not affect the frequency of IDT reactivity in a multivariable model 16 …”
Section: Methodsmentioning
confidence: 99%
“…6,9 However, contrary to previous findings, a recent study examining anti-CCD IgE inhibition in allergic dogs failed to demonstrate improved correlation between the two tests. 20 It therefore would be of interest to compare in vitro serological testing pre-and post-CCD blocking with intradermal testing in horses.…”
Section: Discussionmentioning
confidence: 99%